2021
DOI: 10.7150/ijbs.58657
|View full text |Cite
|
Sign up to set email alerts
|

Protopanaxadiol improves endometriosis associated infertility and miscarriage in sex hormones receptors-dependent and independent manners

Abstract: Background: Patients with endometriosis (EMs) have high risks of infertility and spontaneous abortion. How to remodel the fertility of patients with EMs has always been the hot spot and difficulty in the field of reproductive medicine. As an aglycone of ginsenosides, protopanaxadiol (PPD) possesses pleiotropic biological functions and has high medicinal values. We aimed to investigate the effect and potential mechanism of PPD in the treatment of EMs-associated infertility and spontaneous abortion. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 59 publications
1
15
0
Order By: Relevance
“…It can promote health and prevent diseases by having immunomodulatory [ 63 , 64 ]. This review summarized a therapeutic potential of KRG as an adjunct for treating and preventing endometriosis [ 13 , [25] , [26] , [27] , 29 , 30 ]. Further focused research is needed to reveal the precise functional effect and the mechanism of action of KRG in endometriosis in conjunction with viral spread of pandemic situation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It can promote health and prevent diseases by having immunomodulatory [ 63 , 64 ]. This review summarized a therapeutic potential of KRG as an adjunct for treating and preventing endometriosis [ 13 , [25] , [26] , [27] , 29 , 30 ]. Further focused research is needed to reveal the precise functional effect and the mechanism of action of KRG in endometriosis in conjunction with viral spread of pandemic situation.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 lists active herbal alternative and complementary compounds reported to be effective for endometriosis. A number of studies have been reported that KRG and ginsenosides are effective against endometriosis associated symptoms by regulating angiogenic suppression, increasing apoptosis, immune system regulation, and anti- inflammation [ [24] , [25] , [26] , [27] , [28] , [29] , [30] ]. The following section focused on KRG of its effectiveness for endometriosis.…”
Section: Endometriosis and Herbmentioning
confidence: 99%
See 1 more Smart Citation
“…They then were able to explore the most relevant miRNA in endometriosis [148][149][150]. This information is critical since directed therapies depending on endometriosis may provide new elements to control the inflammatory disease and aid in fertilization [148][149][150][151][152][153][154][155][156][157][158][159][160][161][162][163][164][165][166]. In addition, exosomes contain miRNA and other proteins.…”
Section: Exosomesmentioning
confidence: 99%
“…Waiyaput and coworkers [162] reported that treatment with combined contraceptive pills increased the migration of NK cells, suppressive macrophages, and tolerogenic T cells to the inflamed endometrium of menopause women. In addition, protopanaxadiol, an antioxidant ginsenoside compound, was reported to induce the expression of tolerogenic antigens on NK cells [163]. Thus, hormone therapy radical scavenging causes a protective response in the endometrium.…”
Section: Other Therapiesmentioning
confidence: 99%